Pharmacists' Mental Health during the First Two Years of the Pandemic: A Socio-Ecological Scoping Review - Liam Ishaky; Myuri Sivanthan; Mina Tadrous; Behdin Nowrouzi-Kia; Lisa McCarthy; Andrew Papadopoulos; Basem Gohar (MDPI AG, 2023)
Healthcare workers have been under a great deal of stress and have been experiencing burnout throughout the COVID-19 pandemic. Among these, healthcare workers are pharmacists who have been instrumental in the fight against the pandemic. This scoping review examined the impact of the pandemic on pharmacists' mental health and their antecedents using three databases (CINAHL, MEDLINE, and PsycINFO). Eligible studies included primary research articles that examined the mental health antecedents and outcomes among pharmacists during the first two years of the pandemic. We used the Social Ecological Model to categorize antecedents per outcome. The initial search yielded 4165 articles, and 23 met the criteria. The scoping review identified pharmacists experiencing poor mental health during the pandemic, including anxiety, burnout, depression, and job stress. In addition, several individual, interpersonal, organizational, community, and policy-level antecedents were identified. As this review revealed a general decline in pharmacists' mental health during the pandemic, further research is required to understand the long-term impacts of the pandemic on pharmacists. Furthermore, we recommend practical mitigation strategies to improve pharmacists' mental health, such as implementing crisis/pandemic preparedness protocols and leadership training to foster a better workplace culture.